Understanding Cultural Differences in Innovation: A Conceptual Framework and Future Research Directions. Issue 3 (September 2014) - Kumar, V.
Extant literature on innovation has produced important and significant results. However, no study to date has provided researchers with a framework to understand innovation from a cultural differences perspective. To fill this research gap, the author proposes a framework that categorizes culture and innovation studies into the following six approaches: (1) innovation characteristics, (2) adoption of/propensity to adopt innovations, (3) geographical innovations, (4) market characteristics, (5) learning effect, and (6) organizational functions. Each approach contains two perspectives. From these approaches and perspectives, the author identifies unique and general insights on culture and innovation, discusses the implications of implementing this framework, and recognizes possible areas of further research.